Seismic regime parameters determination of the Oriental Cuba between 1998 and 2007 (2017)
The reseults presentation of the annual evaluation of the seismic regime (years 1998 to 2007) of the oriental region of Cuba with the information registered by the stations of Cuban National Seismological Service. As the starting elements there were used the spatial location of the earthquakes, their magnitudes, depths, curves of energetic unload and their relations magnitude frequency. The evaluation of these statistics allows the analysis of the behavior time-space of the seismic activity. There were introduced comparisons with the determinations realized previously (1979-1989) and the adjustments produced by the changes of the system coverage, during the stage of study, are evaluated.